EFFECTIVENESS OF NUTRITION EDUCATION MEDIA CALENDAR, ANIMATED VIDEO, AND FACEBOOK LIVE IN INCREASING KNOWLEDGE AND ATTITUDES PREVENTION OF ANEMIA IN PREGNANT WOMEN - Aprilia, Salsabila; Fikri, Al Mukhlas; Harianti, Rini (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Anemia is a condition of the body when the hemoglobin (Hb) level is lower than the normal level or less than 11 gr/dl. In pregnant women, anemia has a high influence on the quality of human resources and can endanger the safety of the mother and child. Anemia has various causes, including lack of knowledge about anemia, foods containing iron and Fe tablet supplements. This research aims to determine the effectiveness of nutritional education media calendars, animated videos, and live Facebook in increasing knowledge and attitudes towards preventing anemia in pregnant women in the Cilincing District area. The method used in this research is quasi experimental with a pre-posttest with control group design. The data obtained was then analyzed and processed using Shapiro Wilk normality followed by the paired sample t test for the knowledge variable because the data was normally distributed and the Wilcoxon test for the attitude variable because the data was not normally distributed. The number of respondents who took part in this research was 45 respondents from pregnant women in the Cilincing District, North Jakarta. The results of this study showed that there were significant differences in the level of knowledge and attitudes of pregnant women towards preventing anemia in the three media provided with a p-value of 0.00 (p<0.05).